Prediction of the EMC behaviour of switch mode power supplies in boundary conduction mode including switching frequency limitations - Kübrich, Daniel; Schmidt, Martin; Dürbaum, Thomas (EPE Power Electronics and Motion Control Conference, 2009)
The conducted EMC behavior of a single phase PFC converter operating in boundary conduction mode is predicted by an analytical simulation process. The simulation routines are very flexible in use allowing also for simulation of switching frequency limitations, valley switching and valley skipping. The straight forward simulation process for differential mode disturbances including all blocks of the EMC measurement equipment is described in detail. The benefit of this approach is that it can be adapted to every converter type. In this paper it has been applied to predict the differential mode disturbance level of a PFC boost converter operating in boundary conduction mode. The simulated disturbance levels are compared with results of an EMC measurement on a sample PFC converter. Furthermore, the impact of switching frequency limitations on the differential mode EMI behavior is discussed.
UnivIS-Import:2015-03-09:Pub.2009.tech.IE.lselek.predic
Keywords: EMC/EMI; Modelling; Passive filter; Power factor correction; Switched-mode power supply